(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This research was backed on the researcher’s findings about class XI IPA 3 of SMAN 3 Cimahi whose students had low reading literacy skill in historical learning. More importantly, this skill is important for students to have in historical learning. The main objective of this research was to improve students’ reading literacy skill in historical learning. This class action research was carried out in three cycles, in which each cycle was done in two actions using the John Elliot models. This model processes consists of the stages of planning, action, observation, and reflection. The research findings showed an increase in information literacy skills in each cycle after the implementation of the brain writing method in learning history. This can be seen from the increasingly good scores of each indicator in each cycle. In the first cycle, groups didn’t get the maximum score on each indikator. In the second cycle, a group get the maximum score on several indicators. In the third cycle, all groups get maximum scores on the most of indicators applied in this research. Therefore, it can be concluded that the application of the brain writing method can be used as an alternative to improve students’ reading literacy skills in historical learning in class XI IPA 3 of SMAN 3 Cimahi